Static Recrystallization Kinetics of a Twin-roll Cast AZ31 alloy. (2015) - Ullmann, M.; Graf, M.; Kawalla, R.
Abstract: The static recrystallization (SRX) behaviour of twin-roll cast and annealed magnesium AZ31 strip during hot deformation was determined under deformation conditions corresponding to the hot strip rolling process used in the production of twin-roll cast magnesium coils. Plane strain compression tests were performed using double-hit schedules at temperatures of 250°°C°–°400°°C, strain rates of 1°s -1 °–°10°s -1, and inter-pass times of 1°s°−°400°s, whereby the first deformation step had a logarithmic strain below the critical logarithmic strain necessary for the beginning of dynamic recrystallization. Based on the experimental results, the kinetic equations and grain size model were established. Results show the effects of deformation parameters, including forming temperature and strain rate, on static softening fractions and grain size in the two-pass hot-deformed AZ31 alloy. Deformation-induced precipitations do not hinder the softening processes.